Comparison of Oral Health Related Quality of Life (OHRQoL) in Hypodontia Patients and Patients with Acquired Missing Teeth - Chhetri, Shanti; Ullah Khan, Muhammad Waseem; Yazdanie, Nazia (Journal of Nobel Medical College, 2017)
Background: Hypodontia is the developmental absence of one or more teeth from the dentition whereas acquired missing teeth are those lost due to carries, periodontal problem or dental trauma. Patients with congenitally missing teeth suffer aesthetic, functional and psychological morbidity to various degree through childhood, adolescence and adulthood. Greater understanding of the impact of hypodontia on patient’s quality of life is very important. Oral health related quality of life (OHRQoL) is considered as an outcome measure to evaluate the consequences of edentulism and the available treatment options. Material and Methods: A cross-sectional comparative survey was carried out in the department of Prosthodontics, de’Montmorency College of Dentistry/Punjab Dental Hospital Lahore from 02/03/2010 to 01/09/2010. Total 80 partially dentate patients were studied which included 40 hypodontia patients and 40 patients with acquired missing teeth. All patients were given OHIP-14 questionnaire and responses were recorded on 5-point Likert scale. The mean scores of the two groups were calculated and compared using chi square test. Results: The total OHIP scores in hypodontia patients was more compared to that in patients with acquired missing teeth and difference was significant in the patient group with 4-5 missing teeth. Conclusion: As the missing teeth number increased, it was found that the OHRQoL in hypodontia patients was more impaired compared to the OHRQoL in patients with acquired missing teeth. Journal of Nobel Medical College Volume 6, Number 1, Issue 10 (January-June, 2017), Page: 77-82